Scientific Research Skills Training Needs for Faculty Members at Mathematics Departments at the University of Benghazi - Bothaina Bukhatwa (Utilitas Mathematica, 2025)
The aim of this study is to identify the training needs in the field of scientific research skills for faculty members in the mathematics departments of the Faculties of Science and Education at the University of Benghazi. In addition, the study aimed to examine possible statistical differences in the responses of sample members regarding their training needs for scientific research skills according to variables such as gender, academic rank, specialization, and years of experience. The study used the descriptive analytical method, and a stratified sample of 68 faculty members from the University of Benghazi, Libya, was selected during the fall semester of the academic year 2023/2024.To collect data, a questionnaire consisting of (33) items was developed. The results showed a high level of training needs among faculty members in the mathematics departments at the University of Benghazi in the field of scientific research skills. Moreover, the results indicated that there were no statistically significant differences, at a significance level of (α ≥ 0.05), in faculty members’ responses based on variables such as gender, academic qualification, academic rank, and professional experience. By conducting this research, valuable insights were obtained regarding the training requirements for scientific research skills among faculty members in the mathematics departments at the University of Benghazi. These results contribute to enhancing professional development programs for faculty members in pursuit of excellence in scientific research.